Despotic leadership on happiness at work: Job crafting and optimism as key mechanisms - Alviani, Devi; Dewi, Puspa; Astarina, Ivalaina; Fitrio, Tomy; Perdana, Riky (Asian Management and Business Review, 2026)
The decline in workplace happiness has become an urgent issue in the healthcare sector in the post-pandemic era, particularly within organizations characterized by high job demands and rigid power relations, which have the potential to drain employees’ psychological resources. This situation calls for a deeper understanding of mechanisms that help workers maintain occupational well-being under harmful leadership styles. This research aims to examine the influence of despotic leadership on employee well-being in the workplace, specifically investigating the role of job crafting as a mediator and optimism as a moderator. The study utilizes a quantitative approach supported by a cross-sectional research design. The population includes 286 employees working in healthcare institutions in Riau Province, of which 165 respondents were chosen through systematic random sampling. Data were gathered anonymously through an online survey and processed using structural equation modeling (SEM) with SmartPLS 3.0. The findings reveal that despotic leadership significantly reduces workplace happiness and weakens job crafting behaviors. Job crafting mediates this relationship, as employees who proactively reshape their tasks and workplace relationships report higher levels of workplace happiness. Additionally, optimism moderates the negative effect of despotic leadership on workplace happiness by buffering psychological resource depletion. The novelty of this study lies in testing an integrated model that positions job crafting and optimism as psychological resource recovery and protection mechanisms within the context of dark leadership in the healthcare sector.